A Comparative Study of Transit-Oriented Development Projects in China and the United States - Huang, Jing (My University, 2021)
Transit-Oriented Development (TOD) is an efficient planning tool in dealing with urban sprawl and promoting public transportation implemented across the world. This thesis studies how different TOD cases perform in five various built environment aspects and urban design in China and the United States. The study starts with discussing the TOD definition and some precedents around the world in the literature review. By reviewing some scholarly papers and reports, I developed two different evaluation standards for both the built environment and urban design in TOD communities. With a primarily descriptive analysis of the physical environment, the thesis includes two chapters evaluating the built environment and urban design in different cases. Based on the data from local governments and visual site visits, I can explore the relationship between TOD communities and the whole built environment - how are the TODs’ performances in different built environment aspects, what are the differences between various cases, and how local context promotes the development of a TOD community. Finally, the thesis concludes with some recommendations for future TODs.
Thesis (Master's)--University of Washington, 2021
Keywords: China; Comparative study; the United States; Transit-oriented development; Urban design; Urban morphology; Urban planning; Urban planning